Self repairing bio concrete : a better living - ROLI VERMA,; KIRTI SRIVASTAVA,; R.S.JAGADISH, (International Journal of Pharma and Bio Sciences, 2018)
Concrete is one of the main materials used in the construction industry, with a wide range of use from foundation of a building to the structures of the bridges. The concrete that is generally used has a flaw, that is, its tensile strength is one tenth of the compressive strength and as a result it tends to crack when subjected to tension. Self-healing concrete is a product that will biologically produce limestone to heal cracks that appear on the surface of concrete structures. Bacillus, bacteria along with calcium-based nutrient known as calcium lactate, and nitrogen and phosphorus, are added to the ingredients of the concrete. These self-healing agents can lie dormant within the concrete for up to 200 years. Such spores have extremely thick walls that enables them to remain intact for such long time and spores wait for conducive environment to germinate.They become activated when the concrete starts to crack, food is available, and water seeps into the structure.Then they start feeding on calcium lactate.The consumption of oxygen during the bacterial conversion of calcium lactate to limestone to fix cracks has an additional advantage. Oxygen is an essential element in the process of corrosion of steel and when the bacterial activity has consumed it all, it increases the durability of steel reinforced concrete constructions. bacteria improves the structural properties such as tensile strength, water permeability, durability and compressive strength of the normal concrete. Cracks of various sizes and dimensions can be formed in concrete constructions which are needed to be sealed manually and resulting into the shortening of the life of a particular construction.where as the , Self-healing concrete (SHC) is a revolutionary building material which are capable of solving these problems. They are the future building materials.